Religiosity in Russia: Decomposition into Age, Cohort and Period Effects - Fedotenkov, Igor (Journal of religion and demography, 2023)
Are Russians religious? In this paper, religiosity in Russia (2011–2021) is decomposed into age, cohort and period effects using panel data analysis techniques. It is shown that age effects on religiosity are U-shaped: respondents are more religious when young or old with the minima at the age of 41–45 for women and 46–60 for men. The most religious cohorts in Russia were born in 1960–1980. There is a sharp decline in religiosity in younger generations. There is also a large gender religiosity gap in older generations: women are more religious than men. However, in younger cohorts, the gender religiosity gap closes. Time effects suggest that religiosity in Russia was increasing before 2016, while in 2016, a substantial decline occurred. Since 2016, there has been no growth in religiosity.